An exploration of effectiveness of enterprise development initiatives, in the context of broad-based black economic empowerment, within the McCarthy franchised retail motor dealers in South Africa - Beyer, Buzz (University of Pretoria, 2013)
Dissertation (MBA)--University of Pretoria, 2010.